Respostas

2014-01-20T12:45:16-02:00
3)
3^{x-1} + 3^{x+1} = 30
isso é o mesmo que :
                                           ( considere 3^x = y)
 3^x / 3  + 3^x. 3

y / 3  +  y.3 = 30 ( tire  o mmc = 3)

(y + 9y ) / 3 = 30

10y = 90
y = 9

voltando a informação ( 3^x = y)

3^x = 9

3^x = 3²  ( simplifica o 3)

x = 2

6)  \sqrt[x]{2} = 16^x

2^1/x = 2^4^x        ( simplifica o 2)

1 / x=  4x
1 = 4x²
x² = 1/ 4
x = √1 / √4

x = 1/2

questão 4)

4^x - 3.2^x - 4 = 0

4^x = 2^2^x

2^2^x - 3.2^x - 4 = 0

fazendo 2^x = y

y² - 3y - 4 = 0  ( equação do 2°)

Δ = 25

y1 = 3 + 5 / 2 = ( 4 )
y2 = - 2 / 4 = (- 1 / 2)

voltando aquela informação : 2^x = y

2^x = 2^2

x = 2 


questão 9)

2^2^x - 15.2^x - 16 = 0

fazendo : 2^x = y

y² - 15y - 16 = 0 ( equação 2°)

Δ = 289

y1 = 15 + 17 / 2 ~> 16


2^x = y
2^x = 16
2^x = 2^4

x = 4  Letra E)



2 5 2